Individual variation in migratory movements and winter behaviour of Iberian Lesser Kestrels Falco naumanni revealed by geolocators - Catry, Inês (2012)
The population decline of the Lesser Kestrel Falco naumanni has been the subject of studies across its Western Palaearctic breeding range, but little is known about its use of pre-migratory areas or African wintering quarters. We used geolocators to describe the temporal and spatial patterns of Portuguese Lesser Kestrel migration and wintering behaviour. Data on the complete migration were obtained from four individuals and another three provided further information. Prior to southward migration, Lesser Kestrels showed two different behaviours: northward-orientated movements to Spain and movements in the proximity of the breeding area. Autumn migration took place mostly in late September; spring departures occurred mainly in the first half of February. Wintering grounds included Senegal, Mauritania and Mali, with individuals overlapping considerably in Senegal. Movements registered within the wintering grounds suggest itinerant behaviour in relation to local flushes of prey. During spring migration, birds crossed the Sahara Desert through Mauritania, Western Sahara and Morocco before passing over the Mediterranean to reach Portugal. Autumn migration lasted 4.8 ± 1.1 days, and spring migration lasted 4.1 ± 0.3 days. The mean daily flight range varied between approximately 300 and 850 km for an entire journey of around 2500 km. Effective protection of roosting sites in both pre-migratory and wintering areas and maintaining grasshopper populations in Sahelian wintering quarters appear crucial in preserving this threatened migratory raptor across its African–Eurasian flyway. There was no evidence of any deleterious effects of fitting birds with loggers.